Associação entre depressão, síndrome coronariana aguda e prognóstico intra-hospitalar - Oliveira, Norma Alves de (2011)
The association between depression and acute coronary syndrome (ACS) is common, but it remains underdiagnosed and undertreated, although there is evidence of influence in the poor outcome. The mechanisms defy scientific knowledge. This study investigated the presence of depression, psychosocial factors associated in ACS and the impact on in-hospital prognosis in patients admitted to the Chest Pain Unit of a referral center for cardiology. In a cohort study, 151 patients with ACS, responded to the Beck Depression Inventory and a clinical survey and were followed until hospital discharge. 51.7% (). The frequency of depression in ACS was 51.7% (95% CI: 57.0 to 72.2). Mild depression, moderate depression, dysthymia and atypical depression were statistically significant. In 13% of cases, depression was installed after the coronary event. Family history of ACS (p = 0.04), history of depression (p = 0.006), childhood trauma (p = 0.001), insomnia (p = 0.01), chronic pain (p = 0.004), irritability easy (p=0,005), trauma in adolescence (p=0,003), trauma in adulthood (p=0,0003), personality disorders with emotional instability (p=0,001) and recent trauma (p=0,004), were significantly higher in patients with depression. In multivariate analysis, independent variables associated with depression were trauma in adolescence (0.004), trauma in adulthood (p = 0.001), easy irritability (p = 0.04) and personality disorders with emotional instability (p = 0.03) and acute myocardial infarction (0.02). In-hospital outcomes, acute pulmonary edema (p = 0.01), reinfarction (p = 0.001), recurrent ischemic events (p = 0.0001) were more frequent in the group with depression. These also showed a longer duration of hospitalization (p = 0.001). Depression (oddis ratio (OR) = 5.93, p <0.0001), and ejection fraction, left ventricular (OR = 0.02; p= 0.01.) were predictive of cardiovascular complications. The results suggest an association between depression and ACS. Depression linked existed before the coronary event. Trauma in adolescents and adults, easy irritability, personality disorder, emotionally unstable were psychosocial variables predictive of depression in ACS. Patients with depression are more prone to cardiovascular events in hospital. Depression is a risk factor for ACS and a marker of poor prognosis and SCA can trigger symptoms of depression.